Gayffirmative Action: The Constitutionality of Sexual Orientation-Based Affirmative Action Policies - Peter Nicolas (Washington University Law Review, 2015)
Twenty-five years ago, the U.S. Supreme Court established a consistency principle in its race-based equal protection cases. That principle requires courts to apply the same strict scrutiny to racial classifications designed to benefit racial minorities—such as affirmative action policies—as they do to laws invidiously discriminating against them. The new consistency principle, under which discrimination against whites is subject to strict scrutiny, conflicted with the Court’s established criteria for declaring a group to be a suspect or quasi-suspect class entitled to heightened scrutiny, which focused on such considerations as the history of discrimination against the group and its political powerlessness. As a result of this tension, the Court’s line of precedents for identifying new suspect and quasi-suspect classes has gone dormant, and the Court has not since considered whether any additional such classes exist. Instead, when confronted with plausible candidates for heightened scrutiny, such as gays and lesbians, the Court has engaged in sporadic application of stealth rational basis review. In this Article, I use a hypothetical equal protection challenge to a sexual orientation-based affirmative action policy as a vehicle for proposing a roadmap for harmonizing these competing lines of precedent. I demonstrate that, in light of the consistency principle, an aggrieved heterosexual can bring a challenge to such a policy and seek heightened equal protection scrutiny even though the Court has yet to establish heightened scrutiny for laws discriminating against gays and lesbians. I conclude that such a harmonization of the Court’s equal protection precedents will reinvigorate the Court’s moribund precedents for identifying new suspect and quasi-suspect classes. Moreover, I conclude that announcing heightened scrutiny in such a case would present a particularly appealing vehicle to the Court’s center, represented by Justice Kennedy, whose jurisprudence demonstrates both support for gay rights and hostility toward affirmative action policies.
Keywords: Civil Rights Law; Constitutional Law; Equal protection; Gay rights; Affirmative action